Love Letter to Litla Kongó - Logi Pedro Stefánsson 1992- (2023)
Despite Iceland's reputation as a homogeneous nation, the fact is that Iceland has a history of Icelanders with African heritage traced back to the slave Hans Jónatan, who fled from Denmark to the East of Iceland in 1802. Hans’ story was never documented during his lifetime, and his legacy reduced to folklore. Djúpivogur, where he was welcomed, was later mockingly referred to as "Little Congo". The project is a re-evaluation of Nordic history while celebrating the multicultural communities in modern day Iceland. A collection of objects from contemporary Nordic societies, imagined through the diasporic lens.